Employing control surface model in preliminary aircraft design software - Al-Shamma, Omran; Ali, Rashid; S. Hasan, Haitham (International Journal of Engineering and Technology, 2018)
Many aircraft design software packages are available in the market. Some of them are intended for preliminary design phase. These packages investigate the aircraft stability and controllability through the stability model to get the dimensional and non-dimensional derivatives. For students and fresh engineers, these derivatives are ambiguous and do not give a well-defined consideration about the influence of the control surface sizing on them.Therefore, adding the control surface model to preliminary software will assist, enhance, and improve students' knowledge, sympathy, and investigating studies. This paper presents the control surface model for use in preliminary aircraft design software. The model consists of three sub-models. Each sub-model is involved to perform the sizing of one of the primary conventional control surfaces. The aileron represents the first sub-model. The elevator represents the second sub-model, while the rudder represents the third sub-model. A flowchart for each sub-model is provided.Â